Stressful situations and protective factors: perceptions of teenage girls on socio-educational probation - Simões Matsukura, Thelma; Barboza Cid, Maria Fernanda; Camargo Angelucci, Thamiris; Morais Minatel, Martha (O Mundo da Saúde, 2013)
The goal of this study has been to identify, from the point of view of female teenagers on supervised probation, their own life paths through stressful situations and sources of help and support. Subjects were six teenage subjects, with ages ranging from 15 to 17 years. In order to collect data, we used the following instruments: identification form and half-structured interview guide. Data have been analyzed by means of the Collective Subject Discourse technique. As a result, it has been observed that what the teenagers consider as a support source (such as family and friends) may also be a source of stressful situations. It was verified that difficulties have always been present on the participant’s lives, which highlights the importance of assistance given to these people through preventive policies and interventions that would approach the different contexts of those teenagers.